MUSLIM AND NON MUSLIM FIGURES WHO USE HERMENEUTICS OF THE QUR'AN - Abdul Chalim; Fadloli; Taufik Setyaudin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to find out Muslim and non-Muslim figures who use hermeneutics on the Al-Qur'an. The type of research used is qualitative-descriptive research with a literature review research method. The research results show that non-Muslim figures use hermeneutics to the Al-Qur'an: There are two main non-Muslim figures who use hermeneutics to the Al-Qur'an. With the belief that the quran also has weaknesses like the Bible. So Abraham Giger, accompanied by his student and successor Arthur Jeffry, devoted his life to criticizing the quran. Christoph Luxenberg, Goldhizer and Joseph Schacht their criticism is not only limited to the quran but also the hadith of the Prophet, Saw. Muslim figures who also used hermenutics to interpret the quran include: Muhammad Arkoun, Nasr Hamid Abu Zaid, Hasan Hanafi, Fazlur Rahman, and Muhammad Syahrur. This expert believes that the method of interpreting the quran needs to be adapted to the needs of the people. Because not all Muslims have the ability to interpret the quran, while they still need the quran as a guide for life.